Analisis Persediaan Obat Keras di RSUD Inche Abdoel Moeis Samarinda Menggunakan Metode Economic Order Quantity (EOQ) - Farah Hana Dzakiyah; Rio Haribowo (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
The management of ethical drug inventory is a crucial aspect of supporting the smooth delivery of healthcare services in hospitals. Improper management of ethical drugs can lead to stockouts or overstock, which results increased operational costs and the risk of drug expiration. This study aims to analyze the inventory control of ethical drugs at RSUD Inche Abdoel Moeis Samarinda using the Economic Order Quantity (EOQ), Safety Stock, and Reorder Point methods. The data used in this study are the consumption of ethical drugs during 2024, obtained from the hospital’s Pharmacy Installation. The data analysis method involves calculating ordering and holding costs, determining the optimal order quantity using EOQ, and calculating Safety Stock and ROP to maintain drug availability during lead time. The results of this study indicate that the application of the EOQ method provides a more optimal and efficient order quantity compared to previous policies. Furthermore, Safety Stock and ROP calculations assist the hospital in preventing ethical drug shortages and creating a more structured ordering schedule. Thus, the implementation of EOQ, Safety Stock and ROP methods can improve the efficiency of ethical drug inventory management while supporting the continuity of healthcare services at RSUD Inche Abdoel Moeis Samarinda.